Design and fabrication of cryogenic multiplexing control chip - Huang, Rutian; Shi, Yunfan; Geng, Xiao; Yang, Liangliang; Liu, Jianshe; Chen, Wei (Frontiers in Physics, 2023)
This paper presents a design and fabrication process of a cryogenic multiplexing control chip (MCC) for superconducting quantum computers. The working temperature of MCC can be 10 ∼ 30 mK, because it could be integrated with quantum processor in the same package. With a multiplexing ratio of 1:4 and designed working frequency 4-8 GHz, the MCC is a non-reciprocity device which consisted of bandpass filters and isolators, which are based on tunable inductor bridges (TIB). The MCC chip size is 6 × 6 mm 2 and includes λ /2 coplanar waveguides resonators, superconducting quantum interference device arrays, capacitors, low pass filters, baluns and bias lines. Adopting self-aligned process of Josephson junctions, the fabrication of MCC constitutes four lithography masks. The modular design of MCC could facilitate the development of large-scale superconducting quantum computers.